ANALISIS PENGARUH INOVASI DAN KUALITAS LAPORAN KEUANGAN TERHADAP KINERJA USAHA UMKM KOTA SINGKAWANG - Elita Darmasari; Ahmad Mukoffi; Marija (Universitas Prof.Hazairin,SH Bengkulu, 2025)
The role of MSMEs, particularly small and medium enterprises, is usually linked to government initiatives to reduce unemployment, fight poverty, and equalise wages. The National Medium-Term Development Programme (RPJMN), which must take into account the various ways MSMEs contribute to the nation's economy, is the responsibility of the government. Multiple regression analysis was used as the quantitative research analysis method in this study. Innovations made by MSMEs and the quality of financial reports in accordance with accounting standards have a positive effect on the performance of Singkawang City MSMEs. The results showed that innovation (X1) has a t-count value of 3,178> 2,000 and a significance value of 0.003 <0.05. The quality of financial statements with a t-count value of 2,512> 2,000 and a significant value of 0.017 <0.05. The effect of innovation variables and the quality of financial reports on the performance of MSMEs is 69.8%.